EPISTEMOLOGI ISLAM (Perspektif para Pemikir Islam Maghribi) - Abdul Mukti Ro‘uf (Khatulistiwa, 2013)
Islamic thought – specifically the construction of Islamic epistemology – which lives and develops in the west part of Islam (Spain and North Africa: Marocco, Algiers, Tunisia, and Libya) has distinct characteristics from that of the East (Masyriki). The epistemological pattern of the maghribi (North African) Islam tends to follow the burhani system, a method of reasoning that relies on the power of mind (demontrative, rational syllogism) which originates from the thought of Aristotle. Such though was reflected by figures such as ibn Hazm, al-Syathibi, and ibn Khaldun.